130 Growth and carcass characteristics of short-scrotum, ram, and wether lambs. (29th July 2019) - Schoenian, Susan; Semler, Jeff; David, Gordon; O'Brien, Dahlia; Bennett, Mary Beth; Anderson, Chris
Abstract: Sixty male lambs (East Friesian x Lacaune) from a commercial sheep dairy were used to compare growth and carcass characteristics of short-scrotum (SS), ram (R), and wether (W) lambs. By d 10, every third single, twin, and triplet male was left entire (ram, n = 19), castrated (n = 24), or made short-scrotum (n = 17). After weaning and transport to the Western Maryland Research & Education Center, lambs were maintained as a single group on pasture, with supplemental feeding at 2–3% of BW. Lambs were weighed biweekly. Ultrasonic measurements were determined at d 102. The lambs were slaughtered at d 110. Growth and carcass data were analyzed using PROC GLM and carcass data correlations with PROC CORR. SS lambs had heavier final BW (53.5±1.0 kg) and higher ADG (0.25±0.001 kg/d) than W lambs (50.2±0.6 kg and 0.22±0.001 kg/d, respectively). R lambs were intermediate (51.6±1.0 kg and 0.23±0.001 kg/d, respectively). Sex did not influence ultrasonic backfat (BF), but there was a tendency to influence rib eye area (REA), with W lambs REA smaller than both R and SS lambs (P = 0.07). There was no influence of sex on dressing percentage, body wall thickness, REA, percent kidney and heart fat, leg conformation, or percent boneless closely trimmed retail cuts. There was a tendency (P = 0.10) for SS lambs to have heavier HCW (26.3±0.6 kg) compared to R (24.8±0.6 kg) and W lambs (24.7±0.25 kg). W lambs were fatter (P < 0.02), having greater BF (3.8 ± 0.6 mm) and yield grade (1.9 ± 0.1) than SS (3.0±0.6 mm and 1.6±0.1, respectively) and R lambs (2.8±0.6 mm and 1.5±0.1, respectively). There was strong correlation between ultrasonic and actual carcass measurements (r = 0.7, P < 0.0001), except for REA in SS lambs (r = 0.4; P = 0.1). Compared to W lambs, SS lambs had superior growth and produced leaner carcasses. The short-scrotum procedure may offer a viable alternative to castration.